Society As the Possible Villain in 'Menjelang Magrib': Social Thriller Critical Genre Analysis - R. Hariyani Susanti; Welli Marlisa; Herlinda Herlinda; Aramudin Aramudin (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2023)
The aim of the study is to analyze the Indonesian film Menjelang Magrib released in 2022 using critical genre theory. The movie is potentially a social thriller, where the antagonist is not an individual but rather society. This qualitative research adopts a descriptive approach and will gather data through observation methods with heuristic and hermeneutic readings of selected character dialogues relevant to the topic of analysis. The findings indicate that the society in the film indeed serves as the antagonist, as it discriminates against a person with mental health problems by shackling her and acting selfishly towards the environment. The movie sheds light on the issue of discrimination and environmental degradation and depicts society as the cause of these problems. The use of critical genre theory provides a framework for understanding the societal elements at play in the film and helps to analyze the film's message and purpose. Overall, the study supports the notion that Menjelang Magrib can be analyzed as a social thriller, where society serves as the antagonist.